Cesar's rules : your way to train a well-behaved dog - Millan, Cesar (Crown Archetype, 2010)
In this book the author, a well-known dog trainer takes on the topic of training. In order to provide a variety of training options, he calls upon some of the foremost experts in the field to offer their advice so that you can find the perfect approach that works for you and your dog. It shows you how to communicate well with your dog, and shares the most effective and humane methods for teaching your dog how to be a happy, well behaved member of your household.